Extrusion-cooking techniques : applications, theory and sustainability - Moscicki, Leszek , 1949- (Wiley-VCH Verlag, 2011)
Offering an engineering perspective plus the latest information on the application of this rapidly expanding technique, this practical book covers the technology, engineering, materials and products, as well as economic and ecological aspects. In addition to the theory, it also utilizes case studies that can easily be put into industrial practice